UMP researcher wins WIPO Best Women Inventor’s Special Award at ITEX 2010 - UMP, PNC
Universiti Malaysia Pahang’s (UMP) Dr. Mimi Sakinah Abdul Munaim was the university’s first female researcher to be honored with a Special Award at the World Intellectual Property Organization (WIPO) Best Women Inventor, held concurrently during the 21st International Invention, Innovation & Technology Exhibition 2010 (ITEX 2010) at the Kuala Lumpur Convention Centre on May 14-16 recently.